Kanker Prostat : Risiko dan pencegahannya. - Shintia Christina; Hansel Sanchia; Rebecca Noerjani Angka (Jurnal MedScientiae, 2022)
Prostate cancer is the second most often cancer in male after lung cancer. Risk factor of prostate cancer divided into two, that cannot be modified and that can be modified. Factor that cannot be modified are age, ethnicity/race and family history. Factor that can be modified are anthropometry, smoking, physical activity and diet. Those risk factor established proved to raise the risk of prostate cancer. To prevent prostate cancer by lifestyle, modify, such as diet, physical activity and body weight.